Influence of Teachers' Computing Skills on the Utilization of PMM at SDN 014 Ujung Tanjung, Benai District, Kuantan Singingi Regency - Muslim; Santosa, Firman; Amelia Chandra, Detri (Lembaga Penelitian dan Pengabdian Masyarakat, 2024)
This research concludes a strong correlation between computer proficiency and the utilization of PMM (Pedagogical Media Package) among teachers at SDN 014 Ujung Tanjung, Benai District, Kuantan Singingi Regency, Riau Province, with a correlation coefficient of 0.98. The findings suggest that the higher the computer proficiency possessed by teachers, the greater the utilization of PMM in their teaching processes. The regression equation, Y=0.901X-0.107, provides a mathematical representation of this relationship, indicating that for every one-unit increase in computer proficiency, the utilization of PMM is expected to increase by 0.901 units, with an initial utilization of PMM of -0.107 when computer proficiency is zero. This conclusion underscores the importance of enhancing computer proficiency among teachers to optimize the utilization of PMM in teaching practices. By considering this regression equation, a more focused and sustainable approach to developing teachers' computer skills can be implemented, thus enabling more effective and efficient utilization of PMM to support learning objectives. Therefore, efforts to improve digital literacy and technology skills among educators are crucial for maximizing the potential of technology-enhanced learning in the future.